MARKETING STRATEGY FOR COCKLE FISH PROCESSING PRODUCTS BASED ON DIGITAL MARKETING (STUDY ON RAYHANA REZKY FOOD MSME IN SINJAI REGENCY) - Naufal Asri; Agus Syam; Muhammad Rakib; Nur Halim (Adiba Aisha Amira, 2025)
This study aims to examine the digital marketing strategies used by Rayhana Rezky Food, a micro, small, and medium enterprise (MSME) engaged in cockle fish processing in Sinjai Regency. In response to the growing importance of digital platforms, this research analyzes how digital tools and online media are utilized to enhance market reach and customer engagement. A qualitative descriptive method was applied, with data collected through interviews, observation, and documentation. The findings indicate that the business actively uses social media platforms such as Instagram and Facebook, as well as messaging apps like WhatsApp, for promotional activities, customer interaction, and product dissemination. These digital marketing strategies have helped improve brand awareness and increase product sales. However, challenges remain, including limited digital skills and infrastructure. The study concludes with suggestions for strengthening digital literacy and optimizing e-commerce platforms to support the long-term sustainability of MSMEs in the seafood processing sector.